MARJIN PEMASARAN KELAPA DI DESA PAILELANG KECAMATAN ALOR BARAT DAYA - Emirensiana Latuan; Gerson Maure; Michail Kamaleng (Partner, 2021)
To find out the coconut marketing channel in Pailelang Village, Alor Barat Daya District and to know the marketing margin of coconut in Pailelang Village, Alor Barat Daya District. The data obtained were analyzed by several stages of analysis, namely tracing coconut sales at the farmer to consumer level and using marketing margin analysis. Coconut marketing channels are known that there are 3 (three) coconut marketing channels, namely: Channel I: Farmers - consumers, Channel II: Farmers - Retailers - Consumers and Channel III: Farmers - Village Collectors - Traders - Retailers - Consumers. The marketing margin of coconut in Pailelang Village for Marketing Channel II is Rp. 236,460.67, while in marketing channel III, the marketing margin at the collector level is Rp. 436,460.67 and the marketing margin at retail level is Rp. 736,460.67.  Key Words:  marketing channel, the coconut, Pailelang Village